Therapeutic Potential of Lacidipine against 3- Nitropropionic Acid Induced Huntington's Disease: Based on Molecular Docking, Anti-Inflammatory and Neuroprotective Effects - Alshehri, Samiyah; Afzal, Muhammad; Alqarni, Sana Saeed; Alenezi, Sattam Khulaif; Alharbi, Khalid Saad; Mantargi, Mohammad Jaffar Sadiq; Kazmi, Imran; Sayyed, Nadeem; Imam, Faisal (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Huntington's Disease (HD), a neurological ailment that leads to motor impairment, cognitive decline and psychiatric disorders, has limited treatment options. Hence, there is a pressing demand for new therapeutics to address the complex pathophysiology of HD. Lacidipine, a calcium channel blocker with antioxidative and anti-inflammatory properties, is a promising treatment option. Aims: This work aimed to assess the therapeutic potential of lacidipine against 3-Nitropropionic Acid (3-NPA)-induced neurodegeneration in a rodent model. Materials and Methods: There were 24 male Wistar rats (n=6) were categorized into four groups: the control group, the 3-NPA (10 mg/kg/day) intraperitoneally injected group and two lacidipine groups with dosages of 0.5 mg/kg and 1.0 mg/kg. These treatment animal clusters were exposed to a combination of lacidipine and 3-NPA for 14 days. On the 14th day, behavioral assessments were conducted. Subsequently, on the 15th day of the experiment, all animals underwent anesthesia, followed by the extraction of brain tissue for the evaluation of biochemical parameters, including Lactate Dehydrogenase (LDH), Malondialdehyde (MDA), Superoxide Dismutase (SOD) and Glutathione (GSH). Additionally, the activity of neurotransmitters, such as Acetylcholinesterase (AChE), Gamma-Aminobutyric acid (GABA), glutamate, Dopamine (DA) and inflammatory mediators, including Interleukin-6 (IL-6), Interleukin-1β (IL-1β), Tumor Necrosis Factor-α (TNF-α) and Nuclear Factor kappa-B (NF-kB) were performed. A docking study was conducted to investigate potential interactions between lacidipine and relevant molecular targets AChE (7XN1), D3 receptor (3PBL), GABA (B) receptor (4MQF) and GluA2 receptor (2XHD). Results: Our research showed that treatment of rats with lacidipine after exposure to 3-NPA improved their motor coordination, sensorimotor function and muscular strength. We also observed the restoration of neurotransmitter imbalances, reduced oxidative stress and increased antioxidant defenses in treated rats. Furthermore, lacidipine prevented the upregulation of neuroinflammatory biomarkers induced by 3-NPA. Lacidipine showed a negative binding energy to the target molecules (glutamate: -7.855 kcal/mol, DA: -7.607 kcal/mol, GABA -7.523 kcal/mol and AChE: -6.949 kcal/mol). Conclusion: The research presented in this study offers valuable information regarding the potential of lacidipine to prevent neurodegeneration linked to HD, indicating a promising path for future investigations and possible therapeutic applications to treat this debilitating disease.
Keywords: Antioxidants; Huntington's disease; Inflammation; Oxidative Stress; Neurotransmitters